Efektifitas Asam Folat Dalam Mengurangi Efek Samping Terapi Kasus Toxoplasmosis Dilihat Dari Gambaran Histopatologi Sel Otak Fetus Mencit ( Mus Musculus) Yang Diinfeksi Toxoplasma Gondii - andi jayawardhana; Fauziah Fitri Hernanto; Heni Puspitasari; Mufasirin; Lucia Tri Suwanti (NERSMID : Jurnal Keperawatan dan Kebidanan, 2021)
Period of toddler or early childhood (1-3 years) was the golden period for children development, especially fine motor. Lack of appropriate stimulation at this stage of age can lead to delayed development. Formed of stimulation for toddler was with playing, example playing kinetic sand. It consists various colors, so that will cause interest toddler and they will use their finger skills to shape it. The purpose this study to analyzed effect of playing kinetic sand to the fine motor development of toddler. The design used pre-experiment (one group pre-post test design). The sampling technique was purposive sampling. The location of study was in the Day Care RSUD Dr. Soetomo Surabaya. The period of study started from December 2016 to January 2017. Total population was 60 childrens with a sample size was 21 toddlers. The instrument of study used Activity Program Unit and Denver II. Data analysis used Mc Nemar test. The dependent variable was the fine motor development of toddler and independent variables was playing kinetic sand. The results showed that intervention succeed to improved fine motor development of toddler from 80% (before intervention) to 100% (after intervention). Stimulation of playing kinetic sand was a method to improved the fine motor development of toddlers, so the nurse could socialize it to Day Care and toddler’s parent to used it.